PENYULUHAN PEMANFAATAN LIMBAH PLASTIK SEBAGAI BAHAN BAKAR ALTERNATIF DI SMK TELKOM PEKANBARU - Jusnita Jusnita; Denur Denur; Indra Hasan; Yuhelson Yuhelson; Muhammad Ridha Fauzi; Japri Japri (LPPM UMRI, 2019)
He purpose of this community service is to provide information about the use of plastic waste as alternative fuel for vocational students and Telkom Pekanbaru teachers and to help graduates of vocational students in facing the world of work. The method used is lecture, question and answer, discussion, demonstration. The benefits of this service are; a) Provide scientific contributions, namely theoretical contributions in the form of additional scientific repertoire in the field of engineering studies, especially in the field of studies on the utilization of plastic waste for students of Pekanbaru Telkom Vocational School b) Lecturers can carry out one of the three principles of Higher Education, c) Help the community in unemployment. The results of community service activities broadly include the following components; 1). The success of the target number of participants is more than the planned target. 2) Planning an environmentally friendly movement towards the prosperity and utilization of plastic waste as an alternative fuel in the Final Waste Management Site (TPSA) in Pekanbaru Telkom Vocational High School, 3) The achievement of material targets in this service activity is quite good, because extension materials can be delivered overall 4). Targeted counseling participants as planned before 20 people who majored in TKR and TSM. In its implementation, this activity was attended by 40 participants. Thus it can be said that the target of the participants is reached 100%. This service level has been published in print media (tribune). Keywords: Plastic Waste, Alternative fuel